Wetland spatio-temporal change analysis and ecosystem services in two urbanising cities [Abstract only] - Amerasinghe, Priyanie H.; McCartney, Matthew P.; Apsunde, K.; Mehra, Kanika (2015)
Wetlands in India are under stress due to many natural and anthropogenic events. While the definition of a wetland can extend from small ponds/marshes to large reservoirs, a recent study estimates the wetland area to be 4.7% of country’s geographic area. Key drivers for wetland loss are urbanization and associated land-use changes, population growth and pollution. It is well known that functionally, they provide a variety of ecosystem services (ESS) for human wellbeing and inextricably linked to the hydrological cycle and therefore, the environment as a whole. Usually, wetland loss is assessed only after ground level observations, however, RS/GIS tools offers a way to assess the areas that are rapidly losing wetlands that can be regarded as “Hot spots”. This study was aimed at providing the evidence for wetland loss and showcase the important Ecosystem Services (ESS) they provide, so that planners can take appropriate steps to conserve and safeguard this natural resource. Urban and peri-urban wetlands distribution was studied in two cities, namely, Kolkata, West Bengal, and Nagpur, Maharashtra. Supervised Image classification and Modified Normal Difference Water Index (MNDWI) were used to assess the changes in landscape and loss of wetland area respectively, during the period 2000 and 2013, covering an area of urban sprawl. A wetland inventory was prepared to the extent possible, from the satellite images available in the public domain. A checklist of ESS were prepared through a participatory process (wetland users and key informants) based on the TEEB’s approach to assessing ESS. A total of 27 ESS were selected, based on observations and surveys. Further, in each site, 4 wetlands were investigated to validate the ESS and wetland dependence by poor communities. The satellite images enabled the visualization of wetlands of a size class of 0.36 ha and above. Change analysis for the city of Kolkata indicated an increased land area for built-up areas (6%) and waste/open lands (1%), calculated against the mapped area of 87,500 ha. Decreased coverage was observed for water bodies (3%), orchards and trees (5%), agriculture and shrub lands (10%). Development activities appeared to impact especially the water bodies. Based on wetland inventories and water density maps, 4 types of wetlands appeared to be prominent. These were tanks, aquaculture/paddy rice, riverine marsh/lagoons and treatment units, which covered a total area of 10,645 ha (year 2000). Tanks constituted 12% of the total area, while only 1.2% (127 ha) could be classified as natural. The rest of the area that included much of the EKW (East Kolkata Wetland) was influenced by anthropogenic activities over time. A 50% reduction (5930 ha) in the wetland area was attributed to the loss of aquaculture/paddy rice areas. Interestingly, the EKW area had increased marginally, perhaps due to the conservation efforts through the Ramsar program, although areas close to the city were constantly under threat. While the reduction in the overall area of tanks was marginal, the number of tanks had halved, indicating the impact urbanization has had on the water bodies. Among the 37 wetlands studied in detail, 7 were in the peri-urban areas and were part of the EKW. A rich array of ESS were attributed to the wetlands by the wetland users, where the ESS scores ranged from 4-20, with over 75% receiving scores of 15-17. In the city of Nagpur, the increase in built-up areas was similar to Kolkata (5%). The overall changes in the area for water bodies were marginal. While the agriculture/shrub land area had increased overtime (3%), the vegetation and forest areas (5%), and open/fallow lands (3%) indicated a decline. The sand mines/stone quarry areas remained the same. Four types of wetlands were identified, in the mapped area of 92,500 ha, and they were, tanks, reservoirs, water logged areas in quarries and treatment plants which accounted for over 844 ha. Tanks and reservoirs constituted over 90% of wetland area, and of the 182 wetlands that were mapped only 0.4% could be visualised as natural. Marginal increases in wetland area was attributed to high rainfall and consequent filling up of active quarries and increases in the surface area of tanks, but the loss of natural tanks was significant (70%). Water density maps showed that the southern parts of the city were experiencing water scarcity, probably associated with over abstraction. Eight urban and 4 peri-urban wetland analysis showed a rich diversity of ecosystem functions, with a majority having a range in scores 15-23. Hot spots of wetland loss was clearly evident in both Kolkata and Nagpur, highlighting the need for their conservation. City areas close to the EKW were subject to constant threats, with mounting garbage dumping sites. Considering the rich diversity of ESS of wetlands in both cities, a well-planned conservation program can have benefits that are far reaching.